IL-10 and the resolution of infections - Filippi, CM; von Herrath, MG (The Journal of pathology, 2008)
Chronic viral infections pose serious health concerns, as secondary complications such as immunodeficiencies and cancers are common. Treating such infections with conventional vaccine approaches has proved to be difficult. Studies in animals and humans suggest that vaccine failure is probably due to exhaustion of antiviral T cell responses, which occurs in a number of chronic infections. Attempts to elucidate the causes of impairment of antiviral immunity have pointed to a role for the immunomodulatory cytokine IL-10 in the ability of viruses to establish persistence. Induction of IL-10 production by the host during chronic infection appears to be one of the viral means to alter the class of the antiviral immune response and induce generalized immune suppression. Recent work by us and others suggests that it is possible to resuscitate antiviral immunity by interfering with the IL-10 signalling pathway. Targeting IL-10 thus constitutes a promising alternative to conventional vaccine strategies which have not proved to be successful in treating chronic infections. In addition, sterile cure may be achieved with minimal side-effects by combining agents that alter the IL-10 signalling pathway with other compounds, such as antiviral drugs or interferon, but also agents neutralizing other crucial elements of T cell exhaustion, such as PD-1. Copyright © 2007 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.